A Decision-Aid Tool to Compare Costs of Mechanical Harvesting Systems - Fritz Roka (EDIS)
FE751, a 4-page illustrated fact sheet by Fritz Roka, provides instructions in the use of a Web-based tool to help growers and harvesting contractors organize relevant harvest cost information and then calculate and compare net harvest costs among all available harvesting options. Published by the UF Department of Food and Resource Economics, September 2008.